(untitled) (Research, Society and Development, 2021)
The objective was to know the nurses’ perception and experience about palliative care in the hospital context. This is an exploratory and descriptive study with a qualitative approach. The study included nurses and nurses residing in a public hospital in the state of Rio Grande do Sul, totaling nine professionals from the clinical unit. Data were collected through semi-structured interviews in August 2020. Through the analysis of the data two categories emerged, namely: Palliative Care - complex theme, and Heterogeneous experiences about palliative care.In the first category, it is clear that talking about palliative care is to address a complex theme with different approaches. In the second category, several experiences were reported, showing that, despite being a theme that is still discussed, it ends up being part of the routine of many professionals and families. It is concluded that despite the limited view on palliative care of most professionals, the theme is complex because it outlines biopsychosocio-spiritual aspects of people in terminal situations, in particular, and that the experiences happen in heterogeneous ways. In addition, the statements were relevant to demonstrate that there is weakness in relation to the perception of palliative care, which refers to a possible unpreparedness of the topic.